Anomalous Self‐Optimizing Microporous Graphene‐Based Lithium‐ion Battery Anode from Laser Activation of Small Organic Molecules. Issue 8 (26th June 2022) - Zhang, Binghao; Cheng, Le; Huang, Libei; Tang, Yu; Fang, Yongjin; Li, Tao; Ye, Ruquan; Liu, Qi
Abstract: Laser scribing technology is a straightforward technique to fabricate porous graphene, yet only conducted with polymeric precursors. Compared to polymers, molecular engineering of small organic molecules is much easier, which can be used to modify the graphene with tailored performance. Here we report the first employment of a laser to respectively transform small organic molecules, pentacene quinone and tetraazapentacene quinone (TAPQ), into graphene (P‐LIG and N‐LIG) as high‐performance lithium‐ion battery anodes. The TAPQ, as the N‐fused molecular precursor, produces nitrogen‐doped graphene. Both N‐LIG and P‐LIG exhibit significant self‐enhancement of capacity upon cycling; the N‐LIG anode delivers reversible capacities of 5863 mAh g ‐1 at 0.2 A g ‐1 and retains 1970 mAh g ‐1 at 2 A g ‐1 after another 500 cycles, which is the best performance for the graphene‐type anode. Kinetics studies and structural characterizations verify that the surface‐ and diffusion‐controlled processes are both progressively optimized, providing extra lithium storage upon cycling. It is also supported by small‐angle X‐ray scattering that the disordering level of micropores is increased upon cycling for N‐LIG, corresponding to the enhancement of microporous level. Our work successfully develops a novel facile approach to fabricating heteroatom‐doped microporous graphene exhibiting high performance and provides new insight into the lithium storage mechanism. Abstract : The 3D porous graphene and N‐doped graphene initially synthesized by laser scribing small organic molecules of pentacene quinone (PQ) and tetraazapentacene quinone (TAPQ) exhibit anomalous self‐optimizing capacity upon long‐term cycling. The mechanism of the extra capacity is investigated, which provides novel insight into the lithium storage behavior of porous carbonaceous materials.